Prescribers’ approval rate of pharmacist-initiated interventions to optimise patients’ clinical status of hypertension in the ambulatory care setting - Brajković Andrea; Bićanić Lucija Ana; Orehovački Helena; Prkačin Ingrid; Oliveira Djenane Ramalho De; Mucalo Iva (Acta Pharmaceutica)
This perspective, pre- and post-intervention study with a one-year follow-up primarily aimed to ascertain prescribers’ approval rate of pharmacists’ interventions and clinical status of hypertension following comprehensive medication management (CMM) intervention in the ambulatory care clinic. Between January 2018 and January 2022 overall 100 patients with hypertension and other comorbidities were referred to the CMM services at the Health Centre Zagreb – Centar (HCZC). Out of 275 interventions directed to prescribers, 73.1 % of interventions were approved, 12.4 % were rejected and 14.5 % were not reviewed. The percentage of patients with a blood pressure goal increased from 45 % at the initial consultation to 82.5 % at the patients’ latest encounter (p < 0.001). The average number of drug therapy problems (DTPs) per patient totaled 3.53 ± 1.80, where 98 % of patients had one or more DTPs, 48 % had 4 or more DTPs, whereas 26 % had 5 or more DTPs. Sub-therapeutic dosage (32.6 %) and the need for additional drug therapy (30.9 %) were the two most commonly identified DTPs. These results reinforce the need to integrate pharmacy-led services in the primary care setting with the aim of improving patients’ health outcomes.